(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2023)
Macroglossia in hypertrophy of the organ (tongue) generally without deformation, although on some occasions it may present some alteration in its shape. The different pathologists agree that not all the elements that make up the tongue hypertrophy but it is done at the expense of two tissues: the lymphatic and the muscular with sclerosis of the connective tissue. The appearance of covid-19 has led us to find uncommon symptoms in certain types of patients, such as the one we will show below, a patient in whom macroglossia can be described not so much as a symptom but as a complication, even more so when the patient presents a trauma to the tongue due to placement in the prone position.